Current status of implantable defibrillator devices in patients with left ventricular dysfunction — The first report from the online registry database - Shimizu, Akihiko, MD; Nitta, Takashi, MD; Kurita, Takashi, MD; Imai, Katsuhiko, MD; Kimura, Takeshi, MD; Kobayashi, Yoshinori, MD; Soejima, Kyoko, MD; Niwano, Shinichi, MD; Watanabe, Shigeyuki, MD; Abe, Haruhiko, MD (Journal of arrhythmia, 2008)
Background: The current status of the efficacy of implantable cardioverter-defibrillator (ICD. and cardiac-resynchronization therapy with implantable defibrillator (CRT-D. in patients with left ventricular dysfunction needs to be clarified. Methods and Results: From the Japanese Cardiac Device Treatment Registry database, a total of 1,584 patients who had an LVEF ≦ 40% and had an ICD or CRT-D were selected as subjects in this study. The difference in the clinical characteristics between the primary and secondary prevention groups and the transition of the indications for device implantation over time were examined. Primary prevention gradually increased up to about 50% in all patients. The implantations of ICD/CRT-D for primary prevention in ischemic hear disease was significantly lower than that in dilated cardiomyopathy (33% vs 51%; p < 0.0001). The number of implantations for CRT-D for primary prevention increased dramatically over a one-year period. Conclusions: In Japan, the implantable defibrillator devices for primary prevention was significantly lower in ischemic heart disease compared with dilated cardiomyopathy. Further, an extension of the indications for ICD/CRT-D implantations has recently been occurring, especially with CRT-D devices for primary prevention.